Teleangiectatic osteosarcoma treated by surgery and chemotherapy: a report of 223 affected patients from the Cooperative Osteosarcoma Study Group (COSS) - Bielack, Stefan; Mettmann, Vanessa; Baumhoer, Daniel; Beilken, Andreas; Blattmann, Claudia; Friedel, Godehard; Hardes, Jendrik; Hassenpflug, Wolf; Kager, Leo; Kevric, Matthias; von Kalle, Thekla; Kulozik, Andreas; et al. (Cancer medicine, 2025)
Purpose Teleangiectatic osteosarcoma is a histologic subtype of osteosarcoma that can mimic aneurysmal bone cysts and has so far been incompletely characterized. Patients and Methods We used the database of the Cooperative Osteosarcoma Study Group COSS (patient-registration 1980-2019) to better understand this rare histologic variant. Results 223 eligible patients were identified, 164 having reference pathology (median age 15.9 (3.7-69.7) years; male 134, female 89; tumor sites limb 208 (201 metaphyses, 66 pathologic fractures), trunk 13, head & neck 2; 26 with primary metastases). Known tumor-predisposition syndromes were rare. Therapy included surgery in 215, radiotherapy in 10, and chemotherapy in all patients. Tumor response to preoperative treatment was good in 71% of 165 cases with available data. After a median follow-up of 7.1 (0.2-32.1) years for all patients and 10.5 (0.2-32.1) years for 152 survivors, 5-/10-year actuarial event-free and overall survival expectancies were 61%/57% and 73%/66%, respectively. Five unrelated malignancies occurred during this period. The presence of primary metastases, pathologic fracture, poor response to neoadjuvant chemotherapy, and not obtaining a complete macroscopic remission were associated with inferior outcomes for both event-free and overall survival (p < 0.01). Discussion This large analysis proves teleangiectatic osteosarcoma to be a disease predominantly of the metaphyses of the young. While detected only rarely, the true incidence of genetic tumor predispositions would require prospective assessments. Behaving like other osteosarcoma subtypes in many other ways, this variant may show greater chemosensitivity and hence somewhat better outcomes than other subtypes.
Online veröffentlicht: 9. September 2025
Gesehen am 29.10.2025